(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study analyzed the training needs of agro-dealers on agricultural information dissemination in Kwara State, Nigeria. One hundred and eighty-three (183) agro-dealers were randomly selected for the study. Primary data were collected using a questionnaire. Data collected were analysed using descriptive and inferential statistics. The finding showed that the majority (73.2%) of the respondents were male. The average years of experience in agro-input service delivery was 11 years. The leading agro-inputs and advisory services delivered to farmers by agro-input dealers were insecticides (mean=3.98), improved crop seeds (mean=3.86), and herbicides (mean=3.82). Boric model analysis showed that the topmost ranked training on delivering agro-input services to farmers was storage of viable seeds (Mean Weight Discrepancy Score [MWDS]=1.81), use of viable seeds such as maize (MWDS=1.31), and use of simple agro-equipment maintenance skill (MWDS=0.99). Regression analysis results showed that years of experience (β = 0.112), size of trade (β = 0.626), and access to credit (β = 0.978) were significantly related to the training needs of respondents at the 5% level. The study concludes that training is needed in disseminating agricultural information among agro-dealers and thus needs training to improve their skills in disseminating storage of viable seeds, use of viable seeds, and use of simple agro-equipment maintenance. Therefore, the research recommended that relevant government agencies in collaboration with private/non-government organizations should organize training programmes to improve the skills of agro-dealers in the identified areas.